Unpacking Street Food Tourism in South Africa: A Literature Review and a Way Forward - Erasmus Mzobanzi Mnguni; Andrea Giampiccoli (African Journal of Hospitality, Tourism and Leisure, 2022)
Food tourism is a growing phenomenon that is adding value to the tourism sector. While it can be recognised as a specific food tourism category, street food tourism has not been yet clearly conceptualised and much research remains to be done on this sub-sector. This paper presents an overview of issues relating to street food tourism from a global context. It proposes a definition of street food tourism and suggests strategies to enhance its development. The paper is based on secondary literature. It presents a South African case study which is based on data sourced from a number of websites. The ambition of this paper is to contribute to the expansion of food tourism literature and assist stakeholders in the sector to chart a way forward.